Genetic Diversity Analysis of Couroupita guianensis Aubl.based on RAPD Marker - P, Santosh; Arakera, Suresh B. (Research in Biotechnology, 2017)
Â Couroupita guianensisÂ Aubl. Commonly known as cannon ball tree, belongs to family Lecythidaceae and widely used in Chinese medicine. C. guianensisÂ is being threatened due to habitat destruction in its native range for human settlement and other development related activities. Native populations of C. guianensisÂ were collected from different locations ofÂ the India states and characterized through. To study the genetic diversity of C. guianensisÂ populations we performed RAPD â€“ PCR with several primers. The results are revealed in this study.